Pengembangan Sistem Presensi berbasis Android menggunakan Metode Autogeotagging - Panji Tiara Kusuma; Adam Hendra Brata; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Presence system is a system that will record a person's presence in an institution. There are variose methods in presence system. One of the is fingerprint biometric method. But this method can be contrained if the finger get injured or wet so the sensor can't read the fingerprint. Several attendance methods were implemented, signatures and biometrics authentification. Faculty of Computer Science (FILKOM) Brawijaya University still implements attendance methods such as signatures for students and fingerprint recognition for employees. Particularly for the presence of each employee both FILKOM lecturers and staff are recorded through the existing attendance system. But in its implementation sometimes there are some people who do not attend or forget to attend. This resulted in employees being considered absent. Therefore, This research will focus on an Android based presence system that will use autogeotagging metod. Geotagging is the proses of adding metada about the identity of geographical location. The collection of coordinates uses the Global Positioning System (GPS) which is integrated on mobile devices with the Android operating system.. The location point that has been obtained will be validated to determine whether the point is inside the presence area or not.